Red cabbage (Brassica oleracea) response to hydrogels under drip irrigation and fertigation regimes - N, KISHOR; KHANNA, MANOJ; RAJANNA, G A; SINGH, MAN; SINGH, ANUPAMA; SINGH, SHRAWAN; PARIHAR, C M; PRASAD, SHIV; M, MANU S; KIRUTHIGA, B; J, AROCKIA ANUSTY (The Indian Journal of Agricultural Sciences, 2023)
Water is the main constraint on agricultural output in arid- and semi-arid agroecologies, especially in winter. Hydrogels reduce percolation and evaporation losses in the soil root zone and provide a more continuous stream of moisture to the crop, enhancing water retention. Therefore, the impact of recently developed cross-linked hydrogels (SPG 1118 and Pusa Jal Nidhi) on the performance of red cabbage (Brassica oleracea L.) was studied during 2020–21 and 2021–22 using a spilt-plot design with three replications under drip fertigation. The study results revealed that application of full irrigation (100% ETc) exhibited significantly higher head yield of 16% compared to limited irrigation (75% ETc). Content of NPK in leaf and head were significantly higher under full irrigation (1.31–1.38% of N in head and 2.49–2.62% of N in leaf) compared to limited irrigation. Among modified application of hydrogels, seedling root dipping with hydrogel SPG 1118 exhibited 12% higher head yield over control plots. Application of SPG 1118 recorded 4–5% and 9–14% of higher head yield over Pusa Jal Nidhi and control plots. Likewise, rootapplied SPG 1118 hydrogel had higher plant height, number of leaves, and NPK uptake in head and leaf than soilapplied Pusa hydrogel and control. Due to vertical root development, control plots had longer roots (19.0–20.8 cm) and smaller root volumes (51.8–53.3 g) than hydrogel plots. Thus, root application of SPG 1118 with drip irrigation and fertigation increases hydrogel efficacy and reduces water and nutrient losses from evaporation and deep percolation.